The Qur'anic Perspective Of Surah Al-Humazah Manifests The Values Of Islamic Education - Upiyani; Rumbang Sirojudin; Enung Nugraha; Wasehudin; Susari (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study was inspired by a crisis of Islamic values in education that has been getting worse because of a lack of material things, social and cultural issues, and the loss of Islamic values and principles. There are real beliefs and great examples all around us. As a result, the Qur'an, which is the source of all knowledge, provides resources and useful examples for the development of value-based education. Regardless of the structure of the verse, every verse in the Qur'an has an instructive value that can be explored and expanded. Surah al-Humazah is one of the verses in the Quran that highlights the importance of education. This verse is a threat to anyone who harasses others, promotes untruth and unprofitable information, swears, or gathers money. The study of the educational ideals in the Al-Qur'an al-Humazah letters is the subject of this research, which uses qualitative methodology and focuses on the library research style (library research). To contextualize the values of education in al-Humazah's letter, we need to consider the following: The importance of moral education to God as a servant who is always satisfied with the command of his Creator. It is closely related to the significance of moral instruction to each other (humanity), which ensures that life together is always peaceful, safe, enjoyable, and life. As well as having a sense of sympathy and empathy that is a form of social education values towards each other.